Genetic diversity of native Turkish cattle breeds: Mantel, AMOVA and bottleneck analysis - Öz?ensoy, Yusuf; Kurar, Ercan (Journal of Advanced Veterinary and Animal Research, 2014)
This study was conducted to evaluate potential extinction risk of Turkish native cattle breeds using Mantel and AMOVA tests and Bottleneck analysis. A total of 271 DNA samples were isolated from Anatolian Black, Anatolian Grey, South Anatolian Red, Native Southern Anatolian Yellow, East Anatolian Red, and Zavot cattle. In this study, genotypes of 20 microsatellites were determined by capillary electrophoresis and fragment analysis. A total of 269 different alleles were detected. The maximum and minimum numbers of total alleles were observed in TGLA122 (n=26) and INRA005 (n=7) loci, respectively. The highest average observed and expected heterozygosity values were determined as 0.6190.852 and 0.6690.877, respectively. The average FIS value was 0.068. Results of AMOVA and Mantel tests illustrated statistically significant differences in populations (p<0.001) and correlation (p<0.01). Bottleneck analysis revealed a normal distribution of Lshaped curve indicating that there was no recent risk of extinction for these breeds. DOI: http://dx.doi.org/10.5455/javar.2014.a21 Adv. Vet. Anim. Res., 1(3): 86-93, September 2014